Performing Everyday Things: Ecosomatic Threads of Butoh, Phenomenology, and Zen - Fraleigh, Sondra (Performance Matters, 2024)
This essay engages descriptive, experiential methods of phenomenology, prompts from butoh, and insights of Zen Buddhism. Butoh is the dance and theatre form that arose from the ashes of Japan in the shadow of ecological and social crisis after the Second Word War. It is interpreted widely in current forms that extend well beyond the borders of Japan. The everyday is articulated in the phenomenology of Husserl, Heidegger and Merleau-Ponty, particularly through concepts of “worlding,” how our works ripple out to create a world, as phenomenology and Zen both hold, each in their own way. I write about butoh through a prism of Zen and phenomenology because they share similar philosophical outlooks on performance, and they explain everyday things. In articulating performance of the everyday, this essay takes an ecosomatic turn inward toward matters of consciousness and perception. The writing stems from my participation in butoh as a student, performer, and scholar since 1985, my university teaching of dance and somatics, and my philosophical and lived investigations of phenomenology and Buddhism. Through phenomenology, the essay is descriptive, performative, and concerned with “lived experience,” including how features of experience appear and transform in consciousness.